Investigation of the effects of soluble fibers on the absorption of resveratrol and 2-amino-1-methyl-6-phenylimidazo[4, 5-b]pyridine (PHIP) in the Caco-2 cellular model of intestinal absorption. (18th August 2015) - Willenberg, Ina; Wonik, Jasmin; Schebb, Nils Helge
Abstract: Soluble fibers are known to modulate intestinal absorption of non-polar compounds in the small intestine. Little is known about the modulation of absorption of more polar compounds. In the present study, we applied the Caco-2-transwell-system in order to investigate the modulation of intestinal bioavailability by soluble fibers. The system was tested using pectin and carrageenan as model soluble fibers at a concentration of 0.1% (w/v), which did not compromise the integrity of the cell monolayer. Modulation of absorption was evaluated for the heterocyclic amine aromatic 2-amino-1-methyl-6-phenylimidazo[4, 5-b]pyridine (PHIP) and the polyphenol resveratrol. Neither pectin nor carrageenan reduced the high flux of PHIP, apparent permeability coefficient (Papp ) of 16 × 10 −6 cm s −1 . The low Papp of resveratrol was reduced by both soluble fibers, particularly by pectin. These results suggest that the low bioavailability of polyphenols could be further reduced by soluble fibers. Because of their co-occurrence in several fruits, these findings warrant further research.